Ubiquitous place names; Standardization and study in Indonesia - Lauder, Allan F.; Lauder, Multamia R.M.T. (UI Scholars Hub, 2015)
Place names play a vital role in human society. Names exist in all languages and place names are an indispensible part of international communication. This has been acknowledged by the establishment of the United Nations Group of Experts on Geographical Names (UNGEGN). One of UNGEGN's tasks is to coordinate international efforts on the proper use of place names. Indonesia supports this effort and through its National Geospatial Agency (BIG). Place names are also of interest as an object of study in themselves. Academic studies into place names are found in linguistics, onomastics, philosophy and a number of other academic disciplines. This article looks at these two dimensions of place names, standardization efforts under the auspices of international and national bodies, and academic studies of names, with particular reference to the situation in Indonesia.